E-Upakara, Bebantenan Learning Information System with Tree Diagram Model - Sudana, Anak Agung Kompiang Oka; Putra, I Dewa Nyoman Nurweda; Wirdiani, Ni Kadek Ayu; Taradhita, Dewa Ayu Nadia (Scientific Journal of Informatics, 2020)
Researches on the implementation of information technology in Balinese culture and Hindu religion are still relatively rare, because Balinese culture is often perceived as â€œold fashionedâ€ compared to information technology as something modern. In Hinduism, Yadnya ceremony is a religious ceremony when Hindus expressed gratitude to God, to fellow humans, to the resi, (priest/teacher), to the ancestors, and to Bhuta Kala. The implementation of Yadnya is usually accompanied with bebantenan (offerings) or upakara. Nowadays there are many Hindus, especially the younger generation who do not understand about bebantenan and Yadnya ceremony themselves. This is because information about bebantenan and Yadnya ceremony is relatively difficult to obtain. This paper proposes a multimedia based E-Upakara system or Bebantenan Information System that is a part of E-UpacaraYadnya System. Tree data structure is used to model the informations about data contained in bebantenan, and to illustrare the relations between bebantenan and Yadnya. The system can provide information related to the Yadnya ceremony such as the time the ceremony is held, the ceremony procedures, the bebantenan used during the ceremony, procedures of making bebantenan, videos, and pictures of banten.